Betulinic acid-loaded zein-chondroitin sulfate composite nanoparticles as well as preparation method and application of betulinic acid-loaded zein-chondroitin sulfate composite nanoparticles
The zein-chondroitin sulfate composite nanoparticles, prepared via an anti-solvent method, address the stability and bioavailability issues of betulinic acid, achieving high encapsulation and sustained release for improved anti-tumor activity.
Patent Information
- Application Number
- CN202411290702.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Current delivery carriers based on chondroitin sulfate and prolamin (zein) have limitations in improving the stability and bioavailability of betulinic acid, and there is a need to enhance its anti-tumor activity.
A zein-chondroitin sulfate composite nanoparticle is prepared using an anti-solvent method, with a specific mass ratio of betulinic acid, zein, and chondroitin sulfate, forming nanoparticles with a particle size of 160-190 nm, which encapsulates betulinic acid effectively, enhancing stability and bioavailability.
The composite nanoparticles exhibit a high encapsulation rate of 94.05%, sustained release properties, and improved water dispersibility, leading to enhanced anti-tumor activity against liver cancer cells.
Smart Images

Figure CN119157855A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medicines, and relates to a zein-chondroitin sulfate composite nanoparticle loaded with betulinic acid, and specifically relates to a zein-chondroitin sulfate composite nanoparticle loaded with betulinic acid, and a preparation method and application thereof. Background Art
[0002] Betulinic acid (BA) is a type of pentacyclic triterpenoid component with a relatively special structure. It is the main active ingredient in birch bark, jujube seeds, asparagus, pulsatilla, and syzygium leaves. Modern pharmacological studies have found that betulinic acid has a significant anti-tumor effect and has a significant inhibitory effect on a variety of tumor cells such as lung cancer, ovarian cancer, cervical cancer, breast cancer, and melanoma. Unlike traditional chemotherapy drugs that have a typical killing effect on normal cells, betulinic acid is selective and toxic to human tumor cells, and does not kill healthy cells. Chen Feiyu et al. found that BA can significantly inhibit the proliferation of HepG2, change the cell cycle, and show a significant block in the S phase, causing cell apoptosis, with an apoptosis rate of 10.86% (Chen Feiyu et al., 2017). Betulinic acid can inhibit the proliferation of liver cancer HepG2 cells and induce apoptosis of HepG2 cells. This mechanism may be related to the mitochondrial pathway, which is achieved by blocking cells in the S phase (Li Hao et al. 2019).
[0003] Zein is a food protein widely found in plants. It is easily soluble in 80%-92% ethanol and 70%-80% acetone, but insoluble in water and anhydrous ethanol. Zein forms an α-helix under the hydrogen bonding between the hydroxyl group and the imino group on the peptide main chain. It has unique film-forming properties and is often used as a film-forming material in the food, pharmaceutical and chemical industries. Zein self-assembles in an ethanol-water solution as the solvent evaporates, forming round spheres with a particle size of 250-600nm. During the self-assembly process, part of the secondary structure of zein changes from an α-helix to a β-folded structure. Subsequently, the β-folded structure will be connected end to end under the hydrophobic effect to form a strip, and then the strip will curl into a ring, thereby gradually self-assembling to form nanoparticles. Single zein nanoparticles will aggregate when the salt concentration exceeds 50mM, under neutral conditions, and the storage time exceeds 5d. Biomacromolecule polymers wrapped on the surface of zein can not only improve the stability of zein nanoparticles, but also provide better protection for bioactive components and higher encapsulation efficiency. Biomacromolecule polymers can be polysaccharides and proteins from natural sources, or new polymer materials. Polysaccharides have the advantages of safety, degradability, and low cost and have been widely used. The research on delivery carriers based on protein-polysaccharide complexes has become a research hotspot.
[0004] Chondroitin sulfate (CS) is a sulfated mucopolysaccharide composed of N-acetylgalactosamine and glucuronic acid. It is widely present in the extracellular matrix and tissues of multicellular organisms. The sugar chain is composed of alternating glucuronic acid and N-acetylgalactosamine, and is connected to the serine residue of the core protein through a sugar-like linker region. Chondroitin sulfate has multiple biological activities such as anti-inflammatory, antioxidant and anti-atherosclerotic. In recent years, based on biocompatibility, CS has been used for nano-delivery of hydrophobic and unstable active substances, such as curcumin, proanthocyanidins and β-carotene.
[0005] The invention patent with publication number CN101342179A discloses an anti-tumor Chinese medicine product and a preparation method thereof. The anti-tumor Chinese medicine product includes medicines, reagents, food, and beverages. The effective ingredient of the Chinese medicine product is betulinic acid liposome containing betulinic acid, and the drug encapsulation rate of betulinic acid liposome is more than 90%.
[0006] The invention patent with publication number CN107595809A discloses a zein nano-embedded sustained-release filler and a preparation method thereof, wherein the zein nano-embedded sustained-release filler comprises the following raw materials in parts by weight: 5-15 parts of zein and 2-10 parts of an anti-tumor drug. The anti-tumor drug is one or any combination of cisplatin, doxorubicin, paclitaxel, 5-fluorouracil, etoposide, and vincristine.
[0007] The invention patent with publication number CN111632032A discloses a natural small molecule co-assembled nano drug delivery system and its preparation method and application. The natural small molecule co-assembled nano drug delivery system is a nanoparticle co-assembled from two or more of oleanolic acid, ursolic acid, glycyrrhetinic acid, betulinic acid, betulinol, luperonic acid, lupeol, paclitaxel, rhein, and catechins. The nanocarrier and the drug block cells in different cell cycles, or block the cell cycle in the same cell cycle through different mechanisms, to achieve a synergistic anti-tumor effect and improve the tumor inhibition rate.
[0008] The invention patent with publication number CN113730373B discloses a zeinAOS composite nanoparticle for delivering curcumin and a preparation method thereof. The zein-AOS composite nanoparticles are composed of corn alcohol-soluble protein (zein) and brown algae oligosaccharides (AOS). Curcumin is loaded into the zein-AOS composite nanoparticles to form Cur / zein-AOS composite nanoparticles. The encapsulation rate of curcumin reaches 89.7%, and it has the performance of gastrointestinal sustained release. Curcumin is fully released in the intestinal fluid, and the release rate reaches 83.8%.
[0009] None of the above technologies discloses zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid. Since the current research on delivery carriers based on CS and prolamin is limited, improvements are still needed to improve the stability and bioavailability of betulinic acid and further enhance its anti-tumor activity. Summary of the invention
[0010] The present invention aims at the problems existing in the prior art and provides a zein-chondroitin sulfate composite nanoparticle loaded with betulinic acid and a preparation method and application thereof. The present invention selects anionic polysaccharide CS as a protein particle interface stabilizer, prepares zein-CS composite nanoparticles by an anti-solvent method, and uses them to load betulinic acid. Through process optimization, nanoparticles with high encapsulation rate are prepared, which can improve the bioavailability and anti-tumor activity of betulinic acid.
[0011] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0012] In a first aspect, the present invention provides a method for preparing zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid, which are prepared from betulinic acid, zein and chondroitin sulfate by an anti-solvent method.
[0013] The mass ratio of betulinic acid, zein and chondroitin sulfate is 1-9:1-5:1-5, preferably 2-5:1-5:1-5. Most preferably, the mass ratio of betulinic acid, zein and chondroitin sulfate is 2-5:4:1. In one embodiment, the mass ratio of betulinic acid to zein is 2.5-4.5:5. In one embodiment, the mass ratio of zein to chondroitin sulfate is 1-5:1-5, preferably 1-5:1, and more preferably 4:1.
[0014] The anti-solvent method is a process of forming droplets by dispersing a liquid in another immiscible liquid, also known as a liquid-liquid dispersion method. Zein is dissolved in an ethanol solution and then dispersed in an aqueous phase system at a certain homogenization rate to reduce the solubility of zein, and the molecules aggregate under the action of the self-assembly property, thereby gradually forming nanoparticles.
[0015] The anti-solvent method is specifically:
[0016] Dissolving betulinic acid in an ethanol aqueous solution of zein, wherein the volume fraction of the ethanol aqueous solution is 65-73%, preferably 70%, to obtain a solution 1, wherein the concentration of betulinic acid in the solution 1 is 2.5-4.5 mg / mL;
[0017] The aqueous solution of chondroitin sulfate and the solution 1 are mixed at a volume ratio of 40-60:1 for reaction. The concentration of the aqueous solution of chondroitin sulfate is 0.01-0.1 mg / mL. The reaction time is 0.5-2 h, preferably 1 h, to obtain zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid, named zein@BA-CS.
[0018] In a second aspect, the present invention provides betulinic acid-loaded zein-chondroitin sulfate composite nanoparticles prepared by the preparation method. Preferably, the composite nanoparticles have a particle size of 160-190 nm.
[0019] In a third aspect, the present invention provides the use of the composite nanoparticles or the composite nanoparticles prepared by the preparation method in the preparation of anti-tumor drugs. Preferably, the tumor includes liver cancer.
[0020] Compared with the prior art, the present invention has the following beneficial effects: in the present invention, zein and chondroitin sulfate are combined through protein-polysaccharide to embed betulic acid in an amorphous state inside the particles formed by protein-polysaccharide, and the prepared zein-chondroitin sulfate composite nanoparticles loaded with betulic acid have a stable structure and uniform distribution, a particle size of 160-190nm, an encapsulation rate of 94.05%, excellent sustained-release properties and water dispersibility, better bioavailability, and can improve the anti-tumor activity of betulic acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram for preparing zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid;
[0022] Figure 2 The figure shows the effect of BA concentration on the particle size and encapsulation efficiency of zein@BA-CS, where A is the effect of BA concentration on the particle size of @BA-CS, and B is the effect of BA concentration on the encapsulation efficiency of zein@BA-CS (p<0.05);
[0023] Figure 3 is the XRD pattern of the particles;
[0024] Figure 4 TEM images of the particles, where A is the microscopic image of zein-CS and B is the microscopic image of zein@BA-CS;
[0025] Figure 5 The in vitro release graph and water dispersibility graph of the particles, wherein A is the in vitro release graph of the particles, and B is the water dispersibility graph of the particles (p < 0.05);
[0026] Figure 6The cell activity diagrams of HepG2 cells after 24h and 48h of action of zein@BA-CS nanoparticles, where A is the 24h action diagram and B is the 48h action diagram;
[0027] Figure 7 The results of HepG2 cells phagocytizing coumarin-6 labeled zein@BA-CS nanoparticles, A is the CLSM image, B is the flow cytometry study result, and C is the quantitative result of cell phagocytosis (p < 0.05);
[0028] Figure 8 Immunofluorescence images of microtubules in HepG2 cells after treatment with free BA and zein@BA-CS for 24 hours;
[0029] Fig. 9 Figure 1 is the effect of zein-CS@BA nanoparticles on cell apoptosis, where A is the effect of zein-CS@BA nanoparticles on cell apoptosis after treating HepG2 cells using flow cytometry (cell scatter plot), and B is the percentage of cell apoptosis caused by zein-CS@BA nanoparticles (the sum of the percentage of early and late cell apoptosis) (p < 0.05);
[0030] Fig.10 This is the effect of zein@BA-CS nanoparticles on genes in the Caspase-3 signaling pathway of cell apoptosis (p<0.05);
[0031] Fig.11 This is a diagram showing the effect of zein@BA-CS nanoparticles on proteins in the Caspase-3 signaling pathway of cell apoptosis. DETAILED DESCRIPTION
[0032] It is worth noting that, unless otherwise specified, the raw materials used in the present invention are all common commercially available products, and their sources are not specifically limited.
[0033] Data analysis method: SPSS19.0 was used to analyze the data, and the results were expressed as mean ± standard deviation. One-way analysis of variance was used to test the significance of the test results, and Turkey method was used for multiple comparisons, where P < 0.05 indicated a significant difference.
[0034] Example 1
[0035] Preparation of Zein-Chondroitin Sulfate Composite Nanoparticles Loaded with Betulinic Acid
[0036] 1. Materials and instruments
[0037] (1) Materials: Betulinic acid (BA) with a purity of ≥98% was purchased from Nanjing Chunqiu Biotechnology Co., Ltd.; zein (92% protein content), dimethyl sulfoxide (DMSO), and paraformaldehyde were purchased from Sigma-Aldrich, USA; chondroitin sulfate (CS) was purchased from Shandong Yibao Biological Products Co., Ltd.; potassium bromide (spectral grade) was purchased from Sinopharm Group; coumarin-6 was purchased from Shanghai Myrel Chemical Technology Co., Ltd.; human hepatoma cell HepG2 was purchased from the Chinese Academy of Sciences; fetal bovine serum (FBS), DMEM high-glucose culture medium, and trypsin digestion solution were purchased from Gibco, USA; penicillin and streptomycin were purchased from Harbin Pharmaceutical Group; Triton X-100, bovine serum albumin, CCK-8 kit, and Annexin V-FITC apoptosis detection kit were purchased from Beijing Solebao Company; 5× protein loading buffer, DAPI, and LysoTracker Red were purchased from Xi'an Het Biotechnology Co., Ltd.
[0038] (2) Instruments: nanometer laser particle size analyzer (ZEN3600, Malvern, UK), constant temperature magnetic stirrer (S22-2, Shanghai Siler Instrument Co., Ltd.), transmission electron microscope (JEM-1230, Japan Electronics Co., Ltd.), pH meter (PB-10, Sartorius, Germany), rotary evaporator (R-100, Buchi, Switzerland), high-speed centrifuge (GL-10MD, Hunan Xiangyi Co., Ltd.), freeze dryer (FD5-series, Ximeng International Group Jinximeng Instrument Co., Ltd.), water bath constant temperature oscillator (SHA-BA, Honghua Instrument Factory, Jintan, Jiangsu), carbon dioxide incubator and Fluoroskan multifunctional microplate reader (Thermo Scientific, USA), high performance liquid chromatograph (Agilent, USA), X-ray diffractometer (Bruker, Germany), inverted fluorescence microscope (DMI4000B, Leica, Germany), flow cytometer (Tecan, Switzerland), laser confocal scanner (CLSM, Carl Zeiss, Germany).
[0039] 2. Test methods
[0040] 2.1 Preparation of Zein-Chondroitin Sulfate Composite Nanoparticle Suspension
[0041] 0.5 g of zein powder was added to 100 mL of 70% (v / v) ethanol solution, and magnetic stirring was performed until the protein was completely dissolved to obtain zein solution. 5.00 mg, 2.50 mg, 1.67 mg, 1.25 mg and 1.00 mg of CS powder were weighed respectively, and completely dissolved in 50 mL of distilled water to obtain CS solutions of different concentrations. 1 mL of zein solution was added dropwise to 49 mL of CS solutions of different concentrations with a syringe and stirred for 60 min, so that the mass ratio of zein to CS was 1:1, 2:1, 3:1, 4:1, 5:1, to form a composite nanoparticle suspension, which was a zein-chondroitin sulfate composite nanoparticle (zein-CS nanoparticle) suspension.
[0042] 2.2 Preparation of Zein-Chondroitin Sulfate Composite Nanoparticle Suspension Loaded with Betulinic Acid
[0043] according to Figure 1 The steps are to prepare Figure 1 Schematic diagram of preparing zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid, specifically: add 0.5g of zein powder to 100mL of 70% (v / v) ethanol solution, stir magnetically until the protein is completely dissolved to obtain zein solution, add BA powder to the zein solution so that the final concentration of BA is 2.5, 3, 3.5, 4, and 4.5mg / mL, stir and sonicate at room temperature until BA is completely dissolved to obtain zein nanoparticle solution loaded with BA. Take 1mL of zein nanoparticle solution loaded with BA and add dropwise to 49mL of CS solution with different concentrations with a syringe and stir for 60min, so that the mass ratio of zein to CS is 1:1, 2:1, 3:1, 4:1, and 5:1, to obtain a composite nanoparticle suspension loaded with BA, that is, a suspension of zein-chondroitin sulfate composite nanoparticles (zein@BA-CS nanoparticles) loaded with betulinic acid.
[0044] 2.3 Determination of encapsulation efficiency of zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid
[0045] The encapsulation efficiency of BA was determined by ultrafiltration centrifugation. 1 mL of freshly prepared zein-chondroitin sulfate composite nanoparticle suspension loaded with betulinic acid was added to an ultrafiltration tube with a molecular weight cutoff of 10 KDa. Centrifuge at 4000 rpm for 30 min, remove the filtrate that overflowed the filter membrane, add 1 mL of methanol to the ultrafiltration tube and continue centrifugal extraction. Repeat the above operation twice and combine the filtrate. After filtering through a 0.22 μM organic filter membrane, perform HPLC detection. The detection conditions are as follows: the chromatographic column is a Waters Symmetry C18 column (5 μm, 250 mm × 4.6 mm), the mobile phase is composed of acetonitrile: water (75%: 25%, v / v), the flow rate is 1.0 mL / min, the detection wavelength is 210 nm, and the column temperature is maintained at 30 ° C. The encapsulation efficiency of BA is calculated as follows:
[0046]
[0047] 2.4 Characterization of Nanoparticle Properties
[0048] The particle size, PDI (polymer dispersibility index) and zeta-potential of the obtained zein-chondroitin sulfate composite nanoparticles and zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid were measured: the particle size of the nanoparticles was measured using a nano-laser particle size analyzer, and the nanoparticle suspension samples to be measured were diluted to a certain concentration (diluted 100 times) to avoid the multiple light scattering effect of the nanoparticles. PDI represents the particle size distribution. Generally speaking, the lower the PDI, the more uniform the particle distribution and the more stable the sample. All measurements were carried out at 25°C, at least 10 sets of data were collected for each sample, and the average value was taken after repeated measurements 3 times. The zeta-potential was measured using the Smoluchowski mode, the test temperature was 25°C, and each sample was measured three times.
[0049] 3. Test results
[0050] 3.1 Properties of Zein-Chondroitin Sulfate Composite Nanoparticles
[0051] Both polysaccharide and protein molecules carry charges. When polysaccharide and protein are complexed, the size and properties of their charges are closely related to their mass, and the electrostatic interaction between the two also changes. The change in the ratio of polysaccharide to protein also affects the particle size and PDI (polymer dispersibility index) of the composite nanoparticles. The effect of the mass ratio of zein to CS on the particle size and zeta potential of the composite nanoparticles is shown in Table 1.
[0052] Table 1 Effect of the mass ratio of zein to CS on the properties of zein-chondroitin sulfate composite nanoparticles
[0053]
[0054] The results in Table 1 show that when the mass ratio of zein to CS is 4:1, the particle size of zein-chondroitin sulfate composite nanoparticles reaches the minimum, which is 164.1 nm, and the PDI is less than 0.11. At this time, the protein and polysaccharide are most tightly complexed.
[0055] 3.2 Properties of zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid
[0056] Zein has a large number of hydrophobic region structures, and BA is a hydrophobic compound. When BA binds to zein, there is a hydrophobic interaction between the two. This interaction can last for a certain period of time so that BA is effectively loaded into the carrier. When the BA concentration is 50 μg / mL, the properties of zein-chondroitin sulfate nanoparticles loaded with betulinic acid are shown in Table 2.
[0057] Table 2 Effects of different zein to CS mass ratios on the properties of zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid
[0058]
[0059] As shown in Table 2, under the same BA loading conditions, as the mass ratio of zein to CS increases from 1:1 to 4:1, the particle size of zein-CS composite nanoparticles loaded with BA gradually decreases, from 306.3nm to 189.9nm, and the encapsulation efficiency increases from 70.43% to 94.05%. Further increasing the mass ratio of protein to polysaccharide to 5:1, the particle size of zein-chondroitin sulfate composite nanoparticles loaded with BA shows an increasing trend, which is higher than the particle size of blank nanoparticles at the same mass ratio (180.6nm). When the mass ratio of zein to CS is 4:1, the zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid have a smaller particle size and a higher encapsulation efficiency, and the formed composite structure is more stable and compact.
[0060] The mass ratio of zein to CS was fixed at 4:1, and the BA concentrations were 50 μg / mL, 60 μg / mL, 70 μg / mL, 80 μg / mL, 90 μg / mL, and 100 μg / mL, respectively, to explore the effects of different BA loading amounts on drug-loaded nanoparticles. Figure 2 As shown, Figure 2 Figure 3 is the effect of BA concentration on the particle size and encapsulation efficiency of zein@BA-CS, where A is the effect of BA concentration on the particle size of zein@BA-CS (the horizontal axis represents BA concentration, and the vertical axis represents particle size), and B is the effect of BA concentration on the encapsulation efficiency of zein@BA-CS (the horizontal axis represents BA concentration, and the vertical axis represents encapsulation efficiency).
[0061] Figure 2 The results show that with the increase of BA concentration (50-80μg / mL), the particle size of zein@BA-CS shows an overall decreasing trend. When the BA concentration is 80μg / mL, the particle size of the obtained nanoparticles is the smallest, reaching 190.5nm, and the encapsulation efficiency also reaches the maximum (95.67%). The composite structure formed by zein and CS is more stable and compact, and has a stronger interaction with BA. When the BA concentration increases to 90-100μg / mL, the particle size of the obtained nanoparticles becomes larger and the encapsulation efficiency decreases. This may be because the hydrophobic interaction between hydrophobic compounds and proteins is closely related to the concentration of the two. When the concentration of hydrophobic compounds is low, the hydrophobic interaction maintains the stability of the nanoparticles, and the two are tightly bound. When the concentration of the hydrophobic compound reaches a certain value, the hydrophobic interaction cannot maintain the steady state of the nanoparticles, resulting in its imbalance. The compound escapes from the nanoparticles and attaches to the surface, and the particle size of the nanoparticles increases.
[0062] Example 2
[0063] Sample: the zein-CS nanoparticle suspension obtained in Example 1 with a mass ratio of zein to CS of 4:1; the zein@BA-CS nanoparticle suspension obtained in Example 1 with a BA concentration of 80 μg / mL and a mass ratio of zein to CS of 4:1.
[0064] The crystal structure and microstructure of zein-CS nanoparticles and zein@BA-CS nanoparticles were detected, and the in vitro sustained release and water dispersibility tests of BA were carried out.
[0065] 1. Crystal structure characterization of nanoparticles
[0066] The crystal morphology of the samples was analyzed using an X-ray diffractometer. The zein-CS and zein@BA-CS nanoparticle suspensions were first freeze-dried into powders and placed in an X-ray diffractometer detector for scanning in the range of 10°-60°, at a speed of 5° / min and a current of 40 mA. Zein, CS, and BA of the same mass were used as control samples.
[0067] The crystalline state of BA in the composite nanoparticles was studied by X-ray diffraction. Figure 3 As shown, Figure 3 is the XRD pattern of the particles, Figure 3It shows that the main characteristic peaks of unencapsulated BA appear at 13.61°, 14.28°, and 19.11°, indicating that BA has a crystalline structure and a high degree of crystallinity. The X-ray diffraction pattern of zein has two broad slow peaks at the diffraction angle 2θ of 11.2° and 13.5°, indicating that zein is an amorphous structure. After BA was embedded in the particles, the XRD diffraction patterns of zein@BA-CS nanoparticles did not show the characteristic crystalline peaks of BA, proving that BA was embedded in the particles in an amorphous form. This phenomenon is attributed to the interaction between BA and zein in the particle matrix. After being embedded in the nanoscale polymer matrix, BA changed from its original crystalline structure to an amorphous structure. Compared with zein nanoparticles, no diffraction peak of protein was observed in the composite nanoparticles of zein and CS at 14.5°, indicating that zein and CS interacted.
[0068] 2. Microstructure of Nanoparticles
[0069] The microscopic images of zein-CS and zein@BA-CS nanoparticles were observed using a transmission electron microscope. The suspension of zein-CS and zein@BA-CS nanoparticles was added dropwise onto the copper mesh containing the carbon support film using a pipette, and then observed on the microscope after drying overnight at a voltage of 100 kV.
[0070] The morphology of zein-CS and zein@BA-CS nanoparticles was observed by transmission electron microscopy. Figure 4 As shown, Figure 4 TEM images of the particles, where A is the microscopic image of zein-CS and B is the microscopic image of zein@BA-CS. Figure 4 It can be seen that zein-CS and zein@BA-CS nanoparticles are monodispersed uniform spherical particles, and the introduction of BA does not cause significant changes in the morphology of the nanoparticles.
[0071] 3. BA in vitro sustained release and water dispersibility test
[0072] Preparation of zein@BA nanoparticle suspension: add 0.5g of zein powder to 100mL of 70% (v / v) ethanol solution, stir magnetically until the protein is completely dissolved to obtain zein solution, add BA powder to the zein solution to make the final concentration of BA 4mg / mL, stir and sonicate at room temperature until BA is completely dissolved to obtain zein nanoparticle solution loaded with BA. Take 1mL of zein / BA solution and add dropwise to 50mL of CS solution of different concentrations with a syringe and stir for 60min, so that the mass ratio of zein to CS is 4:1, and obtain a composite nanoparticle suspension loaded with BA, that is, a zein-chondroitin sulfate composite nanoparticle (zein@BA-CS nanoparticle) suspension loaded with BA.
[0073] Preparation of free BA ethanol solution: BA powder was added to 100 mL of 70% (v / v) ethanol solution to make the final concentration of BA 8 mg / mL, and the mixture was stirred at room temperature and sonicated until BA was completely dissolved to obtain free BA ethanol solution.
[0074] In vitro sustained release test of nanoparticles:
[0075] Take the freshly prepared zein-CS@BA suspension, zein@BA nanoparticle suspension and free BA ethanol solution, add 5 mL of each of the above three suspensions to a dialysis bag with a molecular weight cutoff of 14 kDa, and soak it in 25 mL of phosphate buffer solution with a pH of 7.4, and the buffer solution contains 0.2% Tween-80. Then it was shaken on a constant temperature shaker at 100 rpm and 37°C. 1 mL of the buffer solution outside the dialysis bag was taken out at 0 h, 1 h, 4 h, 6 h, 12 h, 24 h, 30 h, 36 h, 48 h, 54 h, 60 h and 72 h of shaking, and supplemented with the same volume of blank buffer. The cumulative release of BA was detected by high performance liquid chromatography. The chromatographic column was a Waters Symmetry C18 column (5 μm, 250 mm×4.6 mm), the mobile phase consisted of acetonitrile: water (75:25%, v / v), the flow rate was 1.0 mL / min, the detection wavelength was 210 nm, and the column temperature was maintained at 30°C.
[0076] Water dispersibility test:
[0077] Zein-CS@BA, zein@BA and BA suspension (BA ethanol solution was directly added to phosphate buffer) were centrifuged at 5000rpm for 10min, the supernatant was filtered through a 0.22μm filter to remove insoluble BA, 1mL of the filtrate was vortexed with 4mL of ethanol for 2min, 15mL of methanol was added to the suspension to extract BA, and the content of BA in the extract was determined by HPLC. The chromatographic column was a Waters Symmetry C18 column (5μm, 250mm×4.6mm), the mobile phase was composed of acetonitrile: water (75:25%, v / v), the flow rate was 1.0mL / min, the detection wavelength was 210nm, and the column temperature was maintained at 30℃. The effect of zein-chondroitin sulfate composite nanoparticles on the water dispersibility of BA was analyzed based on the content of BA in the extract.
[0078] Using free BA as a control, the in vitro sustained release characteristics of BA by zein nanoparticles loaded with BA and zein-CS composite nanoparticles loaded with BA were studied. Figure 5The in vitro release graph and water dispersibility graph of the particles, wherein A is the in vitro release graph of the particles, and B is the water dispersibility graph of the particles (p < 0.05).
[0079] Depend on Figure 5 As shown in Figure A, free BA is rapidly released in the buffer solution, and the BA release is close to 90% after 4 hours. For zein@BA, only about 30% of BA is released after 4 hours, and the BA release of zein@BA-CS is about 20% after 4 hours. After 72 hours of release, about 90% of BA is released in zein@BA, while about 70% of BA is released in zein@BA-CS. It can be seen that zein-CS composite nanoparticles loaded with BA have a more obvious sustained release effect than zein nanoparticles loaded with BA. This is because the hydrophobic interaction between BA and protein exists in a balanced system. Without external interference, BA cannot escape from the system, thereby prolonging the drug release time. In addition, the addition of CS attaches a layer of film to the surface of BA nanoparticles, further hindering the release of BA from the inside of the particles.
[0080] Figure 5 Figure B shows that free BA is difficult to dissolve in water, with a solubility of only 16.17 μg / mL. However, after interacting with proteins and protein / polysaccharides, the solubility of BA in water is significantly increased. Compared with free BA, the solubility of zein@BA in water is increased by 2.27 times, and that of zein@BA-CS is increased by 3.97 times. BA in nanoparticles is easier to disperse in water than free BA. This is because after BA forms nanoparticles with proteins, it wraps BA crystals, resulting in less migration of BA molecules and stronger dispersibility in water. The introduction of CS enables the composite nanoparticles to form a membrane-like structure, which better wraps the BA crystals in the membrane.
[0081] Example 3
[0082] Detection of the antitumor activity of zein-CS nanoparticles and zein@BA-CS nanoparticles
[0083] 1. Cytotoxicity test
[0084] Sample: zein-CS nanoparticles obtained in Example 1 with a mass ratio of zein to CS of 4:1; zein@BA-CS nanoparticles obtained in Example 1 with a BA concentration of 80 μg / mL and a mass ratio of zein to CS of 4:1.
[0085] The CCK-8 kit was used to detect the inhibitory effect of zein@BA-CS nanoparticles on the proliferation of HepG2 cells.
[0086] HepG2 cell culture and treatment method: When resuscitating HepG2 cells, take the cells out of liquid nitrogen, place them in a 37°C water bath and shake them repeatedly to thaw them as soon as possible, then add fresh culture medium to mix, centrifuge to remove the freezing solution and culture medium, add fresh growth medium again, and re-inoculate them in a culture dish, culture at 37°C, 5% CO2 and saturated humidity, and change the medium every 24 hours. The HepG2 cell growth medium consists of 90% DMEM high-glucose medium, 10% fetal bovine blood, and 100U / mL penicillin / streptomycin.
[0087] Dosage group settings: Blank nanoparticles (zein-CS) and zein@BA-CS nanoparticles were dissolved in cell growth medium to obtain zein-CS with concentrations of 0, 10, 20, 40, 80, 160, 320 μg / mL and zein@BA-CS with concentrations of 0, 10, 20, 40, 80, 160, 320 μg / mL, respectively. Cells were treated for 24h or 48h, and 6 parallel experiments were set up for each treatment.
[0088] CCK-8 kit detection steps:
[0089] HepG2 cells were seeded in 96-well plates at a density of 1×10 4 / well, after culturing in the incubator for 24 hours, the original culture medium was discarded, and then 100 μL PBS was added to each well to remove the residual culture medium. Then 100 μL of culture medium containing different concentrations of free BA, blank nanoparticles or drug-loaded nanoparticles was added to the wells, and the culture was continued for 24 hours or 48 hours, with at least 6 parallel tests in each group. The inhibitory effect of BA and its nanoparticles on HepG2 cell proliferation was analyzed using the CCK-8 kit. Add 10 μL of CCK-8 solution to each well, continue to culture for 2 hours, and measure the absorbance at 450nm with an enzyme reader. The cell viability calculation formula is as follows:
[0090] Cell survival rate*(%)=[A S -A0] / [A C -A0]×100
[0091] A S : absorbance of wells with cells, CCK-8 solution, and BA nanoparticles;
[0092] A0: absorbance of wells with culture medium and CCK-8 solution but no cells;
[0093] A C : absorbance of wells with cells, CCK-8 solution but without BA nanoparticles;
[0094] The results of antitumor activity test of zein@BA-CS nanoparticles using CCK-8 method are as follows Figure 6 As shown, Figure 6 These are cell activity diagrams of HepG2 cells after 24h and 48h of action of zein@BA-CS nanoparticles, where A is the 24h action diagram and B is the 48h action diagram.
[0095] Figure 6 The results showed that in HepG2 cells, the empty nanoparticles zein-CS showed little cytotoxicity to HepG2 cells, and the cell survival rate was greater than 90%, indicating that the selected zein and CS carrier materials were safe and reliable. The inhibitory effect of zein-CS composite nanoparticles loaded with BA on the proliferation of HepG2 cells increased with the increase of the dosage concentration and the extension of the treatment time. It can be seen that the anti-proliferation activity of BA on HepG2 cells is time- and concentration-dependent. The half inhibitory concentration (IC50) of HepG2 cells after 24 hours of treatment with zein@BA-CS nanoparticles 50 ) was 38.34±2.19μg / mL. The introduction of CS slightly enhanced its inhibitory effect on HepG2 cell proliferation. After adding CS, the composite nanoparticles could load more BA and improve their anti-tumor activity.
[0096] 2. Cell phagocytosis
[0097] After being embedded in nanoparticles, the way and pathway of small molecule active substances entering cells may change, thus changing their bioavailability. According to the principle of enhanced permeability and retention effect (EPR), small molecule active substances are combined with biomacromolecules such as proteins and polysaccharides to form nanoparticles, which can make small molecule active substances more easily reach and stay in tumor cells. HepG2 cells were used as the research object, and CLSM was used to qualitatively observe the phagocytosis of zein@BA-CS nanoparticles by cells, and the quantitative results were given by flow cytometry. Coumarin-6 has similar solubility to BA and has fluorescent properties, so coumarin-6 was introduced into zein@BA-CS nanoparticles for labeling.
[0098] Sample: zein-CS nanoparticles in Example 1 with a mass ratio of zein to CS of 4:1; zein@BA-CS nanoparticles in Example 1 with a BA concentration of 80 μg / mL and a mass ratio of zein to CS of 4:1.
[0099] Qualitative study: The phagocytosis of BA nanoparticles by HepG2 cells can be observed by confocal laser scanning microscope (CLSM). The inoculation density on the confocal laser culture dish was 1×10 5 After culturing for 24 hours, the culture medium was discarded and rinsed with PBS once, and 2 mL of coumarin-6 labeled zein-CS@BA nanoparticle culture medium (BA concentration was 30 μg / mL) was added, and the culture was continued for 0.5 hours, 2 hours, 4 hours, 6 hours and 12 hours. After discarding the culture medium and rinsing with cold PBS three times, the cell lysosomes were labeled with culture medium containing lysosomal red fluorescent probe (LysoTracker Red) for 1 hour, the culture medium was discarded again and rinsed with cold PBS three times, and the cell nuclei were labeled with culture medium containing DAPI fluorescent dye for 0.5 hours, the culture medium was discarded again and rinsed with cold PBS three times, and then anti-fluorescence quencher was added, and the cells were observed under a CLSM microscope.
[0100] Qualitative study: The phagocytosis of zein-CS@BA nanoparticles by HepG2 cells was detected by flow cytometry. 6 HepG2 cells were seeded in 6-well plates at a density of 100 cells / well. After culturing for 24 hours, the culture medium was discarded and culture medium containing 2.5 mL of coumarin-6 labeled zein-CS@BA nanoparticles (BA concentration was 80 μg / mL) was added. The culture medium was discarded and rinsed with cold PBS three times, then digested with 0.5 mL of trypsin for 2 minutes, the digestion solution was immediately removed, the cells were resuspended with PBS and centrifuged to collect the cells, and then the fluorescence intensity of the labeled cells was detected by flow cytometry.
[0101] Qualitative research and qualitative research results such as Figure 7 As shown, Figure 7 The results of HepG2 cell phagocytosis of coumarin-6 labeled zein@BA-CS nanoparticles, where A is the CLSM image, B is the flow cytometry research result, and C is the quantitative result of cell phagocytosis (p < 0.05); in A, LysoTracker Red emits red fluorescence to represent lysosomes, DAPI emits blue fluorescence to represent cell nuclei, Coumarin-6NP represents coumarin-6, and overlay represents the superposition effect of the two fluorescent signals.
[0102] Depend on Figure 7 As shown in Figure A, the phagocytosis of zein@BA-CS by HepG2 cells is a process where the nanoparticles enter the cells through endocytosis and are mainly distributed in the cytoplasm without entering the nucleus. Figure 7As shown in Figures B and C, the fluorescence intensity in the cells increased significantly with the extension of the incubation time. After 4 hours of phagocytosis by HepG2 cells, the percentage of cells that phagocytized zein@BA-CS nanoparticles did not change significantly, indicating a sustained release effect in the cells.
[0103] 3. Cell Immunofluorescence
[0104] Samples: free BA (30 μg / mL, prepared according to the method of Example 2); zein@BA-CS prepared according to the method of Example 1, wherein the BA concentration is 30 μg / mL and the mass ratio of zein to CS is 4:1.
[0105] 1×10 5 HepG2 cells were seeded at a density of 100 cells / well in a 24-well culture dish. After culturing for 24 hours, the culture medium was aspirated and 1 mL of culture medium containing free BA and zein@BA-CS nanoparticles (BA concentration was 30 μg / mL) was added to each well. The culture was continued for 24 hours. At least 6 parallel experiments were performed in each group. After the culture time was reached, the culture medium was aspirated and rinsed with cold PBS three times. The cells were fixed with 4% paraformaldehyde solution for 30 minutes, and then permeabilized with 0.1% Triton X-100 (1 mL) for 2 minutes. The permeabilization solution was aspirated and discarded. After rinsing with PBS three times, 10% bovine serum albumin was added for blocking for 30 minutes. Then, the primary antibody was added for overnight incubation at 4°C, followed by incubation with FITC-labeled secondary antibody at 37°C for 60 minutes. The cells were rinsed with PBS three times and the cell nuclei were labeled with DAPI for 30 minutes and observed under an inverted fluorescence microscope. The results are shown in Figure 8 As shown, Figure 8 These are the immunofluorescence images of microtubules in HepG2 cells treated with free BA and zein@BA-CS for 24 hours. DAPI emits blue fluorescence to represent the cell nucleus, FITC emits green fluorescence to represent the protein, and Overlay represents the superposition effect of the two fluorescent signals. DAPI, FITC and Overlay are fluorescence microscope images, and CLSM is a confocal microscope image.
[0106] BA mainly causes cytoskeleton collapse by upregulating the expression level of intracellular tubulin, thereby causing cell apoptosis. Immunofluorescence technology is often used to observe the changes in cytoskeleton proteins. Figure 8 The results showed that untreated HepG2 cells had a complete cell microtubule structure, but after being treated with free BA and zein@BA-CS nanoparticles, the cells showed excessive microtubule proliferation, and some cell morphologies were deformed, the cytoskeleton was rearranged, and even collapsed, leading to cell apoptosis.
[0107] 4. Cell apoptosis detection test
[0108] Sample: zein-CS nanoparticles (zein-CS NPs) obtained in Example 1 with a mass ratio of zein to CS of 4:1; zein@BA-CS (zein@BA-CS NPs) prepared according to the method of Example 1, wherein the BA concentration is 20 μg / mL and the mass ratio of zein to CS is 4:1.
[0109] HepG2 cell suspension was inoculated in a 6-well plate at a density of 1×10 6 / well. Place the 6-well plate in an incubator and culture for 24 hours. After the cells adhere to the wall, remove the culture medium and add culture medium containing blank nanoparticles (zein-CS), zein@BA-CS nanoparticles or free BA suspension (BA concentration is 20μg / mL). Set up a blank control. After continuing to culture for 24 hours, aspirate the culture medium, digest with 0.5mL of trypsin, and collect the cells by centrifugation at 1000rpm. Add Annexin V-FITC conjugate (195μL) and Annexin V-FITC (5μL) into a centrifuge tube, then add 10μL PI and shake well. After reacting at room temperature in the dark for 15 minutes, enter the flow cytometer for detection. Analyze the results using FlowJo software. The results are as follows Fig. 9 As shown, Fig. 9 Figure 2 is the effect of zein-CS@BA nanoparticles on cell apoptosis, where A is the flow cytometer detection of the effect of zein-CS@BA nanoparticles on cell apoptosis after treating HepG2 cells (cell scatter plot), and B is a quantitative analysis of the percentage of cell apoptosis caused by zein-CS@BA nanoparticles (the sum of the percentages of early and late cell apoptosis), (p < 0.05).
[0110] Fig. 9 The results showed that there was no significant difference in apoptosis of HepG2 cells after treatment with blank nanoparticles compared with the blank control group. The apoptosis rate of the blank control group was 5.32%, and the percentage of early and late apoptotic cells caused by zein@BA-CS nanoparticle treatment increased to 19.45% (P<0.05), indicating that zein@BA-CS nanoparticles have stronger cytotoxicity relative to HepG2 cells, which is consistent with the previous CCK-8 experimental results. Zein@BA-CS nanoparticles enter cells through endocytosis. After a certain period of time, the accumulated BA in the cells exerts an anti-tumor effect and causes apoptosis of HepG2 cells. There is an adhesive interstitial fluid around the cells. Zein@BA-CS nanoparticles can avoid the influence of the mucus layer through endocytosis, allowing BA to enter the cells smoothly.
[0111] 5. Extraction of total cell RNA and real-time fluorescence quantitative PCR
[0112] Caspase-3 pathway is closely related to cell apoptosis. Caspase-3 and Bax promote tumor cell apoptosis, while Bcl-2 inhibits the process of cell apoptosis. To study the effect of BA composite nanoparticles on Caspase-3, a pathway related to cell apoptosis, the expression of Caspase-3, Bax and Bcl-2 gene mRNA was detected by real-time fluorescence quantitative PCR.
[0113] Sample: zein-CS nanoparticles obtained in Example 1 with a mass ratio of zein to CS of 4:1; zein@BA-CS prepared according to the method of Example 1, wherein the BA concentration is 30 μg / mL and the mass ratio of zein to CS is 4:1.
[0114] HepG2 cells were cultured at a density of 1.0 × 10 5 The cells were inoculated in 12-well plates at a density of 80%. When the cell density reached 80%, zein-CS and zein@BA-CS (BA concentration was 30 μg / mL) were added respectively and the cells were cultured for 48 h. After the incubation, the cells were washed with PBS and the total RNA in the cells was extracted using Trizol reagent.
[0115] The collected cells were lysed into a uniform solution, and then 200 μL of chloroform was added to mix, and the solution was allowed to stand at room temperature for 2 min, and then centrifuged at 12000 rpm for 10 min. The supernatant was mixed with an equal volume of isopropanol, incubated on ice for 15 min, and centrifuged at 12000 rpm for 15 min. The supernatant was discarded, and 1 mL of 75% ethanol was added to wash the precipitate, and the solution was centrifuged at 4°C and 7500 rpm for 5 min. The supernatant was discarded, and the solution was dried at room temperature for 10 min. Finally, 40 μL of DEPC water was added to dissolve the RNA, and the solution was placed in a -80°C refrigerator for use. The RNA concentration was determined using NanoDrop2000, and RNA samples with OD 260 / 280 values between 1.9 and 2.1 were used for subsequent experiments.
[0116] The synthesis of the first strand of cDNA was performed according to the instructions of the RT Reagent Kit with gDNA Eraser reverse transcription kit, and the real-time fluorescence quantitative PCR was performed according to the instructions of the TB Green II kit, with β-actin (actin beta, β-actin) as the internal reference gene. The primer sequences refer to Table 3, and the reaction procedures are as follows: (1) pre-denaturation at 95°C for 30s; (2) reaction at 95°C for 5s to 60°C for 30s, setting 40 cycles; (3) adding a melting curve.
[0117] Table 3 Real-time fluorescence quantitative PCR primer sequences
[0118]
[0119] The results are as follows Fig.10 As shown, Fig.10 This is the effect of zein@BA-CS nanoparticles on genes in the Caspase-3 signaling pathway of cell apoptosis (p < 0.05).
[0120] Fig.10 The results showed that compared with the zein-CS group, the expression of Caspase-3 and Bax genes in the BA-loaded nanoparticle group zein@BA-CS was significantly increased (P<0.05), the expression of Bcl-2 gene was significantly decreased (P<0.05), and the expression of Bax / Bcl-2 was also significantly increased (P<0.05). zein@BA-CS can induce tumor cell apoptosis.
[0121] 6. Extraction of total cell protein and Western blot
[0122] Sample: zein-CS nanoparticles obtained in Example 1 with a mass ratio of zein to CS of 4:1; zein@BA-CS prepared according to the method of Example 1, wherein the BA concentration is 30 μg / mL and the mass ratio of zein to CS is 4:1.
[0123] HepG2 cells were cultured at a density of 1.0 × 10 5 100 μg / mL were inoculated in 12-well plates. When the cell density reached 80%, zein-CS and zein@BA-CS (BA concentration was 30 μg / mL) were added respectively and the cells were cultured for 48 h. After the incubation, the cells were washed with PBS and the intracellular proteins were extracted: (1) The culture medium was aspirated, the cells were rinsed with pre-cooled PBS buffer for 3 times, and 200 μL of RIPA lysis buffer (containing protease inhibitors) was added. (2) The cells were gently shaken to mix, and the cells were scraped off with a cell scraper and collected in a 1.5 mL centrifuge tube. The tube was vortexed for 30 seconds, lysed on ice for 30 minutes, and centrifuged at 4°C, 13,000 rpm for 10 minutes. The supernatant was collected, which was the total cell protein. (3) The concentration of each protein sample was determined using a BCA kit. (4) 5× protein loading buffer was added to ensure that the final protein concentration of each sample was consistent. The samples were boiled in boiling water for 10 minutes to fully denature the proteins. The samples were aliquoted and stored at -80°C for later use.
[0124] Western blot protein expression detection: (1) Absorb 20 μg of total protein for SDS-PAGE electrophoresis. (2) Use a semi-dry transfer device to transfer the target protein band to a PVDF membrane soaked in methanol. After blocking with 5% skim milk powder for 2 hours, incubate the primary antibody overnight at 4°C on a shaker. (3) After washing the membrane 3 times with TBST (15 minutes each time), incubate the secondary antibody for 1 hour on a shaker at room temperature. (4) After washing the membrane 3 times with TBST (10 minutes each time), prepare ECL luminescent solution and use a chemiluminescent imager to detect the target protein band. β-actin was used as an internal reference for relative protein abundance.
[0125] Western blot was used to detect the expression of Bcl-2, Bax and Caspase-3 proteins in HepG2 cells to further explore the effect of BA composite nanoparticles on the Caspase-3 pathway. Fig.11 As shown, Fig.11 Figure 2 is the effect of zein@BA-CS nanoparticles on the proteins in the Caspase-3 signaling pathway of cell apoptosis, where A is the expression of apoptosis-related proteins, and B is the statistical analysis result of apoptosis-related protein expression (p < 0.05).
[0126] Depend on Fig.11 It can be seen that compared with the zein-CS group, the expression levels of Bax and Caspase-3 proteins in the zein@BA-CS group were significantly increased, the expression level of Bcl-2 protein was significantly decreased, and the protein expression level of Bax / Bcl-2 was also significantly increased (P<0.05), indicating that zein@BA-CS nanoparticles can activate the Caspase-3 signaling pathway and induce tumor cell apoptosis.
[0127] There are three main pathways of cell apoptosis: the extrinsic pathway triggered by death receptors on the cell surface; the intrinsic pathway activated by stress conditions such as chemotherapy drugs; and the endoplasmic reticulum stress-induced cell apoptosis pathway. Currently, most studies on apoptosis pathways are focused on detecting the expression levels of several classic apoptosis-related genes and proteins, including Bax, Bcl-2, and Caspase-3. Many apoptosis signal transductions are ultimately caused by Caspase, and Caspase-3 is the final execution gene of apoptosis. Studies have shown that BA can increase intracellular Ca 2+ concentration, leading to mitochondrial membrane potential depolarization and increasing the activity of Caspase-3, Caspase-8 and Caspase-9 to induce apoptosis of cervical cancer cells.
[0128] The above results showed that zein@BA-CS nanoparticles changed the expression levels of apoptosis-related genes and proteins in HepG2 cells, further indicating that zein@BA-CS nanoparticles can induce apoptosis of liver cancer cells.
[0129] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid, characterized in that: The product is prepared from betulinic acid, zein and chondroitin sulfate by using an anti-solvent method.
2. The preparation method according to claim 1, characterized in that: The mass ratio of betulinic acid, zein and chondroitin sulfate is 1-9:1-5:1-5.
3. The preparation method according to claim 2, characterized in that: The mass ratio of betulinic acid, zein and chondroitin sulfate is 2-5:1-5:1-5.
4. The preparation method according to claim 3, characterized in that: The mass ratio of betulinic acid, zein and chondroitin sulfate is 2-5:4:
1.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The anti-solvent method is specifically: Step 1): dissolving betulinic acid in an ethanol aqueous solution of zein, wherein the volume fraction of the ethanol aqueous solution is 65-73%, to obtain a solution 1; Step 2): The aqueous solution of chondroitin sulfate is mixed with the solution 1 to react, so as to obtain zein-chondroitin sulfate composite nanoparticles loaded with betulinic acid.
6. The preparation method according to claim 5, characterized in that: The volume fraction of the ethanol aqueous solution in step 1) is 70-73%.
7. The preparation method according to claim 5, characterized in that: The concentration of betulinic acid in the solution 1 is 2.5-4.5 mg / mL.
8. The preparation method according to claim 5, characterized in that: The concentration of the aqueous solution of chondroitin sulfate in step 2) is 0.01-0.1 mg / mL.
9. The preparation method according to claim 5, characterized in that: In the step 2), the volume ratio of the aqueous solution of chondroitin sulfate to solution 1 is 40-60:
1.
10. The preparation method according to claim 5, characterized in that: The reaction time in step 2) is 0.5-2h.
11. A zein-chondroitin sulfate composite nanoparticle loaded with betulinic acid, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 10.
12. The zein-chondroitin sulfate composite nanoparticles according to claim 11, characterized in that: The particle size of the zein-chondroitin sulfate composite nanoparticles is 160-190 nm.
13. Use of the composite nanoparticles prepared by the preparation method according to any one of claims 1 to 10 or the zein-chondroitin sulfate composite nanoparticles according to any one of claims 11 to 12 in the preparation of anti-tumor drugs.
14. The use according to claim 13, characterized in that: The tumor includes liver cancer.
Citation Information
Patent Citations
Nutritional compositions including a high protein component and exogenous nucleotides
CN102883626A
Preparation method of nano-dispersion system of curcumin loaded by chondroitin sulfate and zein
CN111840253A
Cited By
Rhein and curcumin water-soluble self-assembled nanoparticles as well as preparation method and application thereof
CN121550440A
